Preparation and Reconstruction of Long Branched Palladium Nanowires Exhibiting High Catalytic Activities. Issue 47 (14th December 2018) - Imura, Yoshiro; Kataoka, Hiroki; Akiyama, Ryota; Morita‐Imura, Clara; Kawai, Takeshi
Abstract: Noble metal nanowires prepared by aggregation methods are particularly attractive due to their high catalytic activities. However, the catalytic activities of nanowires tend to be lower due to morphological changes and precipitation. To address this issue, we herein describe a novel method for the construction of long branched Pd nanowires exhibiting a higher catalytic activity than either short Pd nanowires and spherical Pd nanoparticles. However, we found that after standing for 10 d, the catalytic activity was reduced due to a decrease in the nanowire length and the formation of Pd precipitates. Thus, we subsequently demonstrated successful recovery of the catalytic activity by etching and reconstruction using a solution of I − /O2 as the etchant and NaBH4 as the reducing agent. Abstract : We prepared long Pd nanowires (NWs) that exhibited high catalytic activities compared to short Pd NWs and spherical Pd nanoparticles. However, this catalytic activity was lowered upon standing due to morphological changes and the precipitation of Pd. The catalytic activity was subsequently recovered by etching and reconstruction, with the reconstructed Pd NWs exhibiting high catalytic activities.